Mapping the quality competitiveness of human resource management programs: A positioning analysis - Nugroho, Arif Julianto Sri; Marjukah, Anis; Setyawanti, Dandang; Jati, Agung Nugroho; Setianingtyas, Anna Febrianty; Almasitoh, Ummu Hany (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to assess the quality competitiveness of Human Resource Management (HRM) departments at four universities in the Soloraya region of Indonesia through a positioning strategy based on student perceptions of service quality. Research Methodology: Using a quantitative survey method, data were collected from 400 purposively selected students. Multidimensional Scaling (MDS) analysis was applied to ten dimensions of service quality, including trust, quality of education, academic integration, social integration, and various forms of commitment. Validity and reliability tests confirmed the suitability of the instrument, and the data were processed using SPSS software. Results: The analysis revealed three competitive quadrants: Sebelas Maret University in the relatively excellent quadrant, Muhammadiyah University of Surakarta and Batik Islamic University in the challenger quadrant, and Widya Dharma University in the economic cluster quadrant. The results demonstrate clear differentiation in the competitive positioning of HRM programs, influenced by both qualitative and quantitative service quality attributes. Conclusions: Findings highlight the importance of mapping perceptions to identify institutional strengths and weaknesses. Universities with lower positioning need to improve campus facilities, academic environments, and service quality to compete with leading institutions. Limitations: The research scope was limited to four universities in the Soloraya area, and the findings rely solely on student perceptions, which may limit generalizability across other regions or disciplines. Contribution: This study contributes to higher education competitiveness research by applying MDS to HRM programs, offering a novel model for positioning analysis. The results provide strategic insights for university administrators to develop targeted marketing, resource allocation, and quality improvement strategies.